Acceptance of Special Mining Business License by Muhammadiyah : Siyasah Shar'iyyah Perspective - Muhammad Wahdini; Hasse Jubba; Kamsi; Wahdini, Muhammad; Jubba, Hasse; Kamsi, Kamsi (As-Siyasi: Journal of Constitutional Law, 2025)
This research originates from a shift in Muhammadiyah’s stance toward ecological, legal, and political policies in Indonesia. While Muhammadiyah was previously known as a movement critical of natural resource exploitation and unjust environmental policies, in the case of the government’s issuance of the Special Mining Business License (Izin Usaha Pertambangan Khusus or IUPK), it has instead adopted an accepting attitude. This study aims to critically analyze the reasons and normative justifications behind Muhammadiyah’s acceptance of the IUPK through the perspective of Siyāsah Syar‘iyyah, and to examine the transformation of its political-legal position within the ecological context. Employing a normative legal approach, this research collects data through document analysis and in-depth interviews with relevant stakeholders. The findings reveal that, from a ratio legis perspective, Muhammadiyah’s acceptance of the IUPK is driven by the spirit of empowering the people’s economy and the aspiration to serve as a model for equitable and sustainable mining governance. This position is further reinforced by the Majelis Tarjih and Tajdid’s fatwa on mining and energy transition, which does not categorically prohibit mining activities in light of the nation’s dependency on the sector. Within the framework of Siyāsah Syar‘iyyah, this stance may be classified as siyāsah shar‘iyyah ijtihādiyyah—a form of public policy derived from ijtihād to realize the common good (maṣlaḥah ‘ āmmah) as long as it does not contradict the fundamental principles of Sharia